The Impact of Data Mining in Marketing: Transforming Consumer Insights into Business Success - Halkiopoulos, Constantinos (Technium Social Sciences Journal, 2025)
This review paper discusses how data mining can revolutionize the way marketing strategies are drawn, and business is conducted by offering comprehensive consumer insights. Data mining, through techniques such as association rule mining, clustering, and classification, helps businesses understand consumer behavior, forecast sales, optimize campaigns, and improve customer retention. It points out the emphasis on customer segmentation, predictive analytics, and the ethical considerations in data collection and usage, such as private information and AI or machine learning algorithms that bear the imprint of bias. The paper also highlights future trends and advancements in the technology of data mining, with a great emphasis on personalized marketing using a data-driven approach. The paper further stresses the need for ethical applications and careful handling of consumer data to increase trust and build brand loyalty. Overall, this research positions data mining as an essential tool in developing actionable business strategies, enhancing profitability, and reducing costs in the digital marketing landscape.